Characterization of the complete mitochondrial DNA sequence of the Ariosoma meeki (Anguilliformes, Congridae). Issue 3 (2nd July 2020) - Liu, Zhi-Qiang; Shen, Yao-zhong; Zhao, Ming; Wang, Wei; Chen, Wei; Ma, Chun-Yan; Zhang, Feng-Ying; Ma, Ling-Bo
Abstract: In this study, the complete mitochondrial genome of Ariosoma meeki was sequenced, assembled and annotated. The circular genome is 16, 154 bp in length with nucleotide composition is 28.42% A, 26.53% T, 19.65% G, and 25.40% C and contains 13 protein-coding genes (PCGs), 21 transfer RNA genes (tRNAs), 2 ribosomal RNA unit genes and a large non-coding region (putative control region). To further explore the evolution relationship of the Anguilliformes, we constructed the phylogenetic tree and found that the A. meeki had closer relationship with Ariosoma shiroanago . This study provided the valuable evidence on phylogenetic relationship of the A. meeki at the molecular level and essential resource for further study the molecular phylogenetic, biogeography and adaptive evolution of this lineage.